2015
DOI: 10.12720/jomb.4.4.263-269
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Synergy of Collegiate Rowers During 6 Min Maximal Rowing on Fixed and Slides Ergometer

Abstract: The purpose of this study was to evaluate the muscle synergy of collegiate rowers during 6 min maximal rowing on different stretcher mechanisms: fixed (FE) and slides ergometer (SE). The association of muscle synergy to rowing economy and physiological variables was further quantify by statistical analysis. Method:  Ten collegiate rowers were recruited at the end of their competitive season. Muscle synergy was extracted from 16 rowing specific muscles using principal component analysis with varimax rotation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Shaharudin et al analyzed a group of untrained individuals performing rowing movements on slide and fixed ergometers [ 126 ]. The results were consistent with those of previous studies.…”
Section: Ms Application In Sportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shaharudin et al analyzed a group of untrained individuals performing rowing movements on slide and fixed ergometers [ 126 ]. The results were consistent with those of previous studies.…”
Section: Ms Application In Sportsmentioning
confidence: 99%
“…The results were consistent with those of previous studies. Muscle synergies were modulated, but their structure remained the same [ 59 , 126 ]. The CNS had distributed the weights of the muscles differently for rowing on a slide ergometer (leg muscles) and a fixed ergometer (back muscles) to minimize injuries.…”
Section: Ms Application In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…acceleration and EMG were automatically synchronised with Noraxon hardware (Noraxon, DTS Desk Receiver System, Arizona, USA). EMG data were band-pass filtered (bi-directional Butterworth, 10-500 Hz), full wave rectified and low-pass filtered at 8 Hz to obtain linear envelopes (Shaharudin et al, 2014). Baseline EMG amplitude for each muscle was calculated as 3 standard deviations above the mean value from the standing static trial and was removed from the exercise trials for each muscle leaving EMG activity due to exercise only.…”
Section: Electromyographymentioning
confidence: 99%
“…These studies have indicated that the resulted multi-scale oscillations are mode-aligned across channels, and analysis of multiple oscillations is at the same scale. To obtain the synergistic pattern of multiple elements, although component-based algorithms, such as principal component analysis (PCA) ( 26 , 27 ) and independent component analysis (ICA) ( 28 ), have been introduced to extract synergies, non-negative matrix factorization (NMF) is a better choice ( 29 , 30 ) due to its non-negative constraint for all the matrices (the raw matrix and the obtained matrices). A few works have demonstrated that NMF can be used to extract muscle synergies from multi-channel sEMG signals in upper limb muscles during motion tasks ( 31 ), even to obtain activation patterns of muscle-tendon units and time-vary coefficient curves from high-density sEMG signals during dynamic motion tasks ( 32 ).…”
Section: Introductionmentioning
confidence: 99%